Coexistance of Fibromyalgia Syndrome and Conversion Disorder: A Case Presentation - Saime Ay; Haydar Gök; Yeşim Kurtaiş; Ayşe Küçükdeveci; Hakan Kumbasar (Archives of Rheumatology, 2007)
Conversion is loss of function in motor or sensory organs without any underlying pathology. Psychological disturbances may simulate typical symptoms of musculoskeletal conditions and cause controversy in diagnosis and management. It should be remembered that despite the presence of an organic cause for musculoskeletal symptoms, conversion disorder may coexist and complicate the treatment. In this paper, a 17 years old female patient who had typical musculoskeletal symptoms and diagnosed to have fibromyalgia syndrome together with conversion disorder is presented. (Rheumatism 2007; 22: 144-6)